Urban Rivers: Catalysts for Sustainable Cityscapes: Sungai Perkotaan: Katalisator untuk Lanskap Kota yang Berkelanjutan - Yousif Abbas Yousif; Khaled Abdulwahab (Academia Open, 2024)
This study investigates the impact of urban rivers on city identities, focusing on their dual nature as both natural and constructed elements. By applying Kevin Lynch's theoretical framework to riverfronts in Iraq, we uncover how these areas, despite their strategic importance, are often overlooked in urban planning. Our methodology combines a literature review with a case study analysis to explore the distinctive attributes of riverfronts that contribute to the mental image of cities. The findings reveal that riverfronts not only enhance the visual and experiential quality of urban environments but also suggest that they could serve as key components in strategies aimed at improving urban sustainability and quality of life. This research highlights the potential of riverfronts to transform urban planning paradigms, emphasizing the need for greater integration of these spaces in city development initiatives. Highlights: Riverfronts blend natural and urban elements, shaping city perceptions. Often neglected, riverfronts hold central economic potential. Strategic enhancement improves sustainability and urban quality of life. Keywords: Urban Sustainability, Riverfront Development, Mental Image, Urban Planning, Environmental Design